Editorial : special issue on “artificial intelligence for future wireless communications and networking” - Tang, Jianhua (2019)
Recent breakthroughs in Artificial Intelligence (AI) and Machine Learning (ML), including deep neural networks, the availability of huge amount of data, and powerful computing platforms are providing us with technologies to perform tasks that once seemed impossible. The recent win of AlphaGo over the world champion Mr. Lee Sedol has witnessed the power of AI beyond what many of us can imagine. In the near future, autonomous vehicles, intelligent mobile networks, and intelligent internet-of-things will become a norm and AI will be one of the key technologies to make all these possible. Therefore, we forsee that AI can provide many new and unprecedented opportunities in the way we design our wireless and wired data pipelines, the way we manage and optimize our wireless and wired networks, and the way we manage and deliver different user services and user content.